A Case Study of Genomic Instability in an Industrial Strain of Saccharomyces cerevisiae. Issue 11 (1st November 2018) - Rodrigues-Prause, Aline; Sampaio, Nadia M V; Gurol, Theodore M; Aguirre, Guadalupe M; Sedam, Hailey N C; Chapman, Mary J; Malc, Ewa P; Ajith, V P; Chakraborty, Parijat; Tizei, Pedro A; Pereira, Gonçalo A G; Mieczkowski, Piotr A; et al.
Abstract: The Saccharomyces cerevisiae strain JAY270/PE2 is a highly efficient biocatalyst used in the production of bioethanol from sugarcane feedstock. This strain is heterothallic and diploid, and its genome is characterized by abundant structural and nucleotide polymorphisms between homologous chromosomes. One of the reasons it is favored by many distilleries is that its cells do not normally aggregate, a trait that facilitates cell recycling during batch-fed fermentations. However, long-term propagation makes the yeast population vulnerable to the effects of genomic instability, which may trigger the appearance of undesirable phenotypes such as cellular aggregation. In pure cultures of JAY270, we identified the recurrent appearance of mutants displaying a mother-daughter cell separation defect resulting in rough colonies in agar media and fast sedimentation in liquid culture. We investigated the genetic basis of the colony morphology phenotype and found that JAY270 is heterozygous for a frameshift mutation in the ACE2 gene ( ACE2 /ace2 -A7 ), which encodes a transcriptional regulator of mother-daughter cell separation. All spontaneous rough colony JAY270-derived isolates analyzed carried copy-neutral loss-of-heterozygosity (LOH) at the region of chromosome XII where ACE2 is located ( ace2 -A7/ace2 -A7 ). We specifically measured LOH rates at the ACE2 locus, and at three additional chromosomal regions in JAY270 and in a conventional homozygous diploid laboratory strain. This direct comparison showed that LOH rates at all sites were quite similar between the two strain backgrounds. In this case study of genomic instability in an industrial strain, we showed that the JAY270 genome is dynamic and that structural changes to its chromosomes can lead to new phenotypes. However, our analysis also indicated that the inherent level of genomic instability in this industrial strain is normal relative to a laboratory strain. Our work provides an important frame of reference to contextualize the interpretation of instability processes observed in the complex genomes of industrial yeast strains.